Institutions and Development in the MENA region : Between Economic Growth Challenges and Political Instability - Ayass, Hamza; Zouiri, Hassane (Acta Universitatis Danubius. Œconomica, 2024)
The main goal of this paper is to study the effect of governance on economic growth . Our main focus is on the 17 Middle Eastern and North African (MENA) countries during the period 2002-2018. Using a dynamic panel System GMM approach by Blundell and Bond (1998). We found insignificant effect of Governance on economic growth in the MENA countries. The nature of the relationship between growth and governance explains the outbreak of the "Arab Spring" in some countries of the region which revealed pervasive corruption, especially in the political sector, also the region have been vulnerable to global, financial and political crises, negatively impacting its prospects of economic growth.